Old adults and educational practices : the case of a Portuguese Third Age University - Veloso, Esmeraldina (2011)
The present work sets itself to study the educational activities aimed at the elderly within an non-formal educational context, more specifically within the framework of a Third Age University. According to the two main theoretical perspectives responsible for shaping the discussion and practices in the education of the elderly, namely the perspective of functionalist educational gerontology and the critical educational gerontology theories, the current study aims at equating the different educational activities that were developed within a Third Age University. Some lines of thought of the functionalist perspective such as the theory of activity assume that the elderly must keep active in order to avoid decline. Such envisaged activities are extensions of the activities undertaken during the working years and are believed to be beneficial to the retirees. However, this new busy and dynamic way of living the later years, involved in different educational, cultural and recreational activities is not a reality for all the elderly but is rather close to those with a Middle Class social standing. The analysis of Lenoir (1979) as well as Guillemard (1972) shows how the social practices of the retirees are conditioned by their respective social standing and the differences in the capital accrued through their lives, especially during the working years. Therefore, the access to culture and education can be limited to a restricted number of retirees and elderly. On the other hand, critical gerontology aims at changing the situation regarding the education for the elderly, allowing for a real change in the lives of the elderly as well as a democratisation in their access to culture and education. Within this theoretical framework, the education of the elderly is not perceived as just a way to “kill time” or “avoid ageing” but something that overcomes these goals without denying them or rendering them impossible. It aims at the transformation of the reality of each student within the concept of a liberating education according to Freire or „empowerment‟ according to Cusack. These theoretical approaches allowed us to analyse a Third Age University in respect to its educational project and prevailing underlying educational theory, the objectives its set out to achieve, the educational practices and its intended student population. We chose to undertake an empirical investigation inspired on the same methodology principles as the case study, as it allows for an understanding of the social processes that take place within the non-formal education context. This way, research took the shape of an ethnographic type study where fieldwork techniques were used such as observation, interviews and documentary research, among others. The fieldwork took place from April 2001 to October 2002. One of the conclusions of the present study is that the “traditional” and “classical” school model is only partially rejected and we cannot say that the University‟s educational/cultural project is guided by the liberating and emancipating education principles of Freire or the ones adapted by Glendenning and Battersby for the education of the elderly. It was also found that the university caters for a privileged group of elderly with a middle class social standing.